2020
DOI: 10.1002/tal.1799
|View full text |Cite
|
Sign up to set email alerts
|

Integrated optimal wind‐resistant design of super‐tall structures with toggle‐brace damper systems

Abstract: With the increasing heights of super-tall buildings, the natural frequency of these structures approaches the predominant frequency of winds, causing the structures to be more sensitive to wind load. For the safety and economy of these structures, the formulation of a reasonable wind-resistant design is crucial. In this paper, an optimal design of toggle-brace damper systems for super-tall buildings using a damping ratio limit method is presented to obtain the optimal placement, number, and damping coefficient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…6,7,16 is that the damper was directly installed at the beam–column joint. Since then, the two kinds of TBDS have been extensively studied based on the small deformation solution 18–24 …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…6,7,16 is that the damper was directly installed at the beam–column joint. Since then, the two kinds of TBDS have been extensively studied based on the small deformation solution 18–24 …”
Section: Introductionmentioning
confidence: 99%
“…Since then, the two kinds of TBDS have been extensively studied based on the small deformation solution. [18][19][20][21][22][23][24] However, it is hard to clarify the influence of the geometry parameters of TBDS on the its performance comprehensively based on the small deformation solution. The geometric sensitivity and the amplification capacity are two aspects of the TBDS.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…e TBD allows fluid viscous dampers to function at small displacements of the structure, and the effectiveness of such devices has been verified by experimental and theoretical studies. Several studies on the application of TBDs and the optimization of their form have shown that the application of TBDs can be effective in reducing the vibration response of structures [21][22][23]. Huang [24] summarized various types of displacement amplification mechanisms of elbow-joint supports.…”
Section: Introductionmentioning
confidence: 99%